Flexible Lasers: A Thin‐Film Flexible Defect‐Mode Laser (Advanced Optical Materials 8/2020). Issue 8 (17th April 2020) - Ali, Taimoor; Lin, Jia‐De; Snow, Benjamin; Wang, Xiuze; Elston, Steve J.; Morris, Stephen M.
Abstract : The back‐cover picture, referring to the article number 1901891 by Taimoor Ali and co‐workers, illustrates the beam steering from a flexible defect‐mode liquid crystal laser that is fabricated using a facile film transfer method. The laser demonstrates a low threshold fluence of 12.3 ± 0.5 µJ cm −2 per pulse. Beam steering is observed when the flexible laser is subjected to a mechanical deformation that shows potential for wearable and flexible technologies.